Taste Perception in School Children: Is There an Association with Dental Caries? - Egil Edibe; Menteş Ali (Balkan Stomatological Society, 2020)
Background/Aim: Individuals make food choices based on a number of physiological, nutritional, environmental and socioeconomic factors but sensory qualities of food namely the taste has priority as the determinant in food selection. The purpose of the study is to evaluate sweet, salty, sour and bitter taste perceptions of school children and compare them in term of caries experience.